The chorioallantoic membrane (CAM) assay for the study of human bone regeneration: a refinement animal model for tissue engineering - Moreno-Jiménez, Inés (Sci Rep, 2016)
Biomaterial development for tissue engineering applications is rapidly increasing but necessitates efficacy and safety testing prior to clinical application. Current in vitro and in vivo models hold a number of limitations, including expense, lack of correlation between animal models and human outcomes and the need to perform invasive procedures on animals; hence requiring new predictive screening methods. In the present study we tested the hypothesis that the chick embryo chorioallantoic membrane (CAM) can be used as a bioreactor to culture and study the regeneration of human living bone. We extracted bone cylinders from human femoral heads, simulated an injury using a drill-hole defect, and implanted the bone on CAM or in vitro control-culture. Micro-computed tomography (μCT) was used to quantify the magnitude and location of bone volume changes followed by histological analyses to assess bone repair. CAM blood vessels were observed to infiltrate the human bone cylinder and maintain human cell viability. Histological evaluation revealed extensive extracellular matrix deposition in proximity to endochondral condensations (Sox9+) on the CAM-implanted bone cylinders, correlating with a significant increase in bone volume by μCT analysis (p < 0.01). This human-avian system offers a simple refinement model for animal research and a step towards a humanized in vivo model for tissue engineering.